Rites of the Republic citizens' theatre and the politics of culture in Southern France - Ingram, Mark, 1957- (Teaching culture., 2011)
In this exploration of citizenship and the politics of culture in contemporary France, Ingram examines two theatre troupes in Provence: one based in a small town in the rural part of the Vaucluse region, and the other an urban project in Marseille, France's most culturally diverse city. Both troupes are committed to explicitly civic goals in the tradition of citizens' theatre. Focusing on the personal stories of the theatre artists in these two troupes, and' the continuities between their narratives, their performances, and the national discourse directed by the Ministry of Culture, Ingram examines the ways in which these artists interpret universalistic ideals underlying both art and the Republic in their theatrical work. In the process he charts the evolution of new models far society and citizenship in a rapidly changing France. --Book Jacket.